2021
DOI: 10.1038/s41598-020-79664-6
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ enhances the therapeutic effect of mesenchymal stem cells on experimental renal fibrosis

Abstract: Mesenchymal stem cells (MSCs) administered for therapeutic purposes can be activated by interferon-γ (IFN-γ) secreted from natural killer cells in injured tissues and exert anti-inflammatory effects. These processes require a substantial period of time, leading to a delayed onset of MSCs’ therapeutic effects. In this study, we investigated whether pretreatment with IFN-γ could potentiate the anti-fibrotic ability of MSCs in rats with ischemia–reperfusion injury (IRI) and unilateral ureter obstruction. Administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…This conversion to the active form might require several days. Therefore, prior to administration, preconditioning with various factors, including cytokines [ 17 , 18 ], hypoxia [ 19 , 20 ], pharmacological compounds [ 21 , 22 ], and genetic modification [ 23 , 24 ], has been widely studied to enhance the therapeutic effects of MSCs. We have previously reported that MSCs cultured in STK (Kanto Chemical, Tokyo, Japan), which is serum-free medium containing growth factors for MSC culture, promote their immunosuppressive ability by increasing the expression of tumor necrosis factor-α-induced protein 6 (TSG-6) and inducing polarization of immunosuppressive M2 macrophages, thereby enhancing their anti-fibrotic effect [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This conversion to the active form might require several days. Therefore, prior to administration, preconditioning with various factors, including cytokines [ 17 , 18 ], hypoxia [ 19 , 20 ], pharmacological compounds [ 21 , 22 ], and genetic modification [ 23 , 24 ], has been widely studied to enhance the therapeutic effects of MSCs. We have previously reported that MSCs cultured in STK (Kanto Chemical, Tokyo, Japan), which is serum-free medium containing growth factors for MSC culture, promote their immunosuppressive ability by increasing the expression of tumor necrosis factor-α-induced protein 6 (TSG-6) and inducing polarization of immunosuppressive M2 macrophages, thereby enhancing their anti-fibrotic effect [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, Fariba et al suggested the IFN-γ-peptidomimetic fibroferon targeted to PDGFβR-overexpressing myofibroblasts attenuates renal fibrosis [88]. Ryo et al showed that interferon-γ enhances the anti-fibrotic effect of mesenchymal stem cells (MSCs) on experimental renal fibrosis, and it is through the secretion of prostaglandin E2 that MSCs can exert a protective effect on rats subjected to ischemia-reperfusion injury (IRI) and UUO [89]. In recent years, studies from Patrícia et al suggest that, besides NK (through IFN-γ) and dendritic cells (through IL-12), CD8 + T lymphocytes, as another source of IFN-γ, likewise enhances CD4 + Th1 phenotype development [90].…”
Section: Ifn-γ-producing Cd8 + T Cells In Renal Fibrosismentioning
confidence: 94%
“…Additionally, recent studies demonstrated that MSC culture in vitro and preparation prior to transplantation might affect the therapeutic properties. Indeed, two independent studies showed that the use of BM-MSCs pretreated with melatonin or IFNγ ameliorated interstitial fibrosis compared with control groups [198,199]. Similarly, amniotic fluid-derived stem cells (AFSCs), which exhibit characteristics of both ESCs and MSCs, preconditioned with GDNF, were shown to abrogate the degree of renal interstitial fibrosis in mice [200].…”
Section: Renal Fibrosismentioning
confidence: 99%